Go-Scufy: Redesain Produk Sepatu Wanita Berbahan Karung Goni Menggunakan Metode Quality Function Deployment - Catur Endah Sulistiyoningrum; J. Jufrizal; Adam Mulia (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2017)
Creative industry is a cycle of creation, production, and distribution of goods / services using creativity and intellectual capital as the main input. The creative industry can improve the welfare and create new jobs for the community. The object of this research is a shoe manufacturer. In general, shoes made using synthetic raw materials so that shoes products tend not environmentally friendly. Many alternative natural materials are more environmentally friendly to replace this synthetic product, one of which is a burlap sack. This research is doing redesign of women's shoe sack with Quality Function Deployment method. The results of the house of quality matrix are design targets including: good quality and durable materials, shoe prices, concept of sneaker shoe, external sole material and insole, combination of dark and bright colors, batik inner/outer appearance is different, display design can be replaced, shoe fin section can be removed pairs, the main material of burlap sack, there is a waterproof parachute; and multifunctional shoes.